2020
DOI: 10.1021/acsenergylett.0c00522
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Cation–Lattice Interaction and Dynamics in Triple-Cation Perovskites Revealed by Infrared Vibrational Nanoscopy

Abstract: Hybrid organic–inorganic perovskites exhibit extraordinary photovoltaic performance. This is believed to arise from almost liquid-like low-energy interactions among lattice ions and charge carriers. While spatial variations have recently been identified over multiple length scales in the optoelectronic response of perovskites, the relationship between the heterogeneity and the soft cation–lattice interactions has remained elusive. Here, we apply multivariate infrared vibrational nanoimaging to a formamidinium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 74 publications
(161 reference statements)
1
38
0
Order By: Relevance
“…Such disordered polaron–cation coupling is likely associated with a non-uniformity in the dynamic lattice elasticity. This interpretation is supported by other recent experimental and theoretical investigations 59 , 60 , 62 , 63 , which have identified a heterogeneity in chemical composition and resulting local lattice disorder and strain in perovskite films. With HPP IR s -SNOM probing the excited-state vibrational absorption, we resolve spatial heterogeneities in polaron–cation coupling arising from lattice disorder, which directly impacts polaron formation, lifetime, transport and, as such, photovoltaic device performance.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Such disordered polaron–cation coupling is likely associated with a non-uniformity in the dynamic lattice elasticity. This interpretation is supported by other recent experimental and theoretical investigations 59 , 60 , 62 , 63 , which have identified a heterogeneity in chemical composition and resulting local lattice disorder and strain in perovskite films. With HPP IR s -SNOM probing the excited-state vibrational absorption, we resolve spatial heterogeneities in polaron–cation coupling arising from lattice disorder, which directly impacts polaron formation, lifetime, transport and, as such, photovoltaic device performance.…”
Section: Resultssupporting
confidence: 80%
“…As another unique aspect, lead halide perovskites exhibit heterogeneity over multiple length scales in their optoelectronic responses in, e.g., photoluminescence intensity, carrier lifetime, or open circuit voltage 11 . While several works have addressed the nanoscale heterogeneity in the lattice strain and elasticity in the electronic ground-state 59 , 60 , the direct relationship between the nonuniform optoelectronic response and the underlying polaronic heterogeneity has not yet been established. Ultrafast infrared vibrational spectroscopy has previously elucidated the coupling between a molecular cation and a photoinduced polaron in perovskites 35 , 61 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Perovskite films used in solar cells or light emitting diodes (LEDs) are intrinsically heterogeneous. [ 1,2 ] They typically consist of grains, that are of different sizes, have varying surface and/or bulk defect numbers, and exhibit different interactions with other grains. The heterogeneity is particularly large when perovskite films contain nanoparticles or other low‐dimensional structures where spatial confinement changes the state energies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Larger binding energy of ≈40 meV was evaluated for MAPBr 3 perovskites. [ 10 ] Exciton binding energies in 2D perovskites are of the order of hundreds of meV, [ 2,11,12 ] consequently the majority of charge carriers in these structures are expected to be bound in excitons. Therefore, efficient charge carrier generation and their mobility still remain important issues limiting performance efficiency of solar cells utilizing 2D perovskites.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond optical response in the visible range, additional information from the material can be identified from the infra-red region using near-field technique. Recently, infrared vibrational spectroscopic studies have shown label-free chemical information and cation vibrational dynamics in liquids (258) and perovskites (259), respectively.…”
Section: Discussionmentioning
confidence: 99%